Silver Nanoparticle Coated Bioactive Glasses - Composites with Dex/CMC Hydrogels: Characterization, Solubility, and In Vitro Biological Studies - Wren, A.W.; Hassanzadeh, P.; Placek, L.M.; Keenan, T.J.; Coughlan, A.; Boutelle, L.R.; Towler, M.R. (John Wiley & Sons, 2015)
Silver (Ag) coated bioactive glass particles (Ag-BG) were formulated and compared to uncoated controls (BG) in relation to glass characterization, solubility and microbiology. X-ray diffraction (XRD) confirmed a crystalline AgNP surface coating while ion release studies determined low Ag release (<2 mg/L). Cell culture studies presented increased cell viability (127 and 102%) with lower liquid extract (50 and 100 ml/ml) concentrations. Antibacterial testing of Ag-BG in E. coli, S. epidermidis and S. aureus significantly reduced bacterial cell viability by 60-90%. Composites of Ag-BG/CMC-Dex Hydrogels were formulated and characterized. Agar diffusion testing was conducted where Ag-BG/hydrogel composites produced the largest inhibition zones of 7 mm (E. coli), 5 mm (S. aureus) and 4 mm (S. epidermidis). This study presents the synthesis of AgNP coated bioactive glass particles which are incorporated into Dex/CMC hydrogels for localized therapeutic effects. Solubility profiles are determined in addition to evaluating toxicity levels in eukaryotic cells. Additionally, antibacterial properties are evaluated in microbes such as S. aureus, E. coli, and S. epidermidis.